Uji Validasi Rancangan Aplikasi Kelengkapan Resume Medis di Klinik Almeta Medika - Yunita, Nirma; Persadha, Galih; Husin, Husin (Jurnal Kesehatan Indonesia, 2023)
The quality of medical records becomes more valuable if the information written is complete, especially on the medical resume. Complete medical resume writing at Almeta Medika Clinic Banjarmasin has not been carried out, this causes patient information to be incomplete. So a complete medical resume application was designed. This research aims to validate the complete medical resume application at the Almeta Medika Clinic, Banjarmasin. This research method is descriptive qualitative, collecting data using questionnaires and checklists. The subjects in this research were medical records officers, Almeta Medika Banjarmasin clinic managers, IT expert respondents and materials experts. The results of this research were that by testing it was found that the design of the ERD, DFD and application for complete medical resumes at the Almeta Medika Banjarmasin Clinic contained a login, dashboard, 4 components of quantitative analysis and the results of quantitative analysis reports/summaries. ERD and DFD were created using Microsoft Visio and the medical resume application was created using Microsoft Access after identifying user needs and identifying data requirements. The complete medical resume application at Almeta Medika Clinic Banjarmasin has been designed according to the clinic's needs. Validation with medical records officers, Almeta Medika Banjarmasin clinic manager, IT expert respondents and material experts found the appropriate category. Validation testing of the medical resume completeness application at Almeta Medika Clinic Banjarmasin is designed according to the clinic's needs and is feasible to implement.